Penerapan Metode Incremental Pada Aplikasi Laporan Pengawas di LRT Sumsel - Diva Mariska; Ahmad Syazili; Ahkmad Ipandy (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The supervisor reporting process at the South Sumatra Light Rail Transit Management Agency (Balai LRT Sumsel) was previously conducted using paper-based forms, making report management less efficient and increasing the risk of recording errors, document loss, delayed information delivery, and difficulties in retrieving archived reports. This study aims to develop a web-based Supervisor Report Application to support a more effective and well-organized reporting process. The system was developed using the Incremental method, in which each development stage included requirements analysis, system design, implementation, and testing. Google Apps Script was used as the backend, Google Sheets as the database, and HTML, CSS, and JavaScript to develop the user interface. The application implements Role-Based Access Control (RBAC) by providing separate access privileges for Officers, Administrators, and Management. System performance was evaluated through Black Box Testing using twelve test scenarios covering the application's primary functions. The testing results confirmed that all functions operated properly and satisfied the defined functional requirements. The developed application simplifies digital reporting, improves report management and data recapitulation, provides statistical information, and supports report export in PDF and Excel formats. These results indicate that the Incremental method is well suited for developing a web-based reporting system that meets the operational needs of Balai LRT Sumsel..